Komunikasi Eufemisme dalam Berita Penembakan Brigadir J pada Media Online Detik.com dan Kompas.com - Muh. Salman Rafiq; Puji Laksono (Asosiasi Seni Desain dan Komunikasi Visual Indonesia, 2024)
The results of the research obtained showed that the use of euphemisms was used as a support, in 10 news stories found as many as 372 words, namely 161 in Detik.com news, and 211 words in Kompas.com news with their respective uses. The forms of euphemisms used are metaphors, initials, acronyms, uptake, foreign languages, and periphrases. Furthermore, the audience's perspective is determined by the framing made on the news using metaphors, catchphrases, exemplars, depictions, visual images, roots and appeal to principle. In Detik.com news the perspective of the audience is made with Brigadier J as the victim, while in the news Kompas.com the perspective of the audience is directed at Brigadier J as the perpetrator because of the issue of sexual harassment.